IT stereotypes in television shows - Forgasz, Helen (2013)
Despite over 20 years of Information Technology (IT) intervention programs, the proportion of females in the discipline has decreased this century. The depiction of the IT profession on television is a significant source of information about IT careers and may influence student career decisions. In this study, the ways in which male and female IT expert characters were portrayed in five television shows were examined and compared. While many existing stereotypes were challenged, all IT expert characters displayed some stereotypical characteristics, with IT technicians portrayed in the most stereotypical way. Female characters were not as stereotypical as males; but also not well recognised. We posit that the male “geek” technician stereotype overshadows any alternative depictions of IT professionals and reinforces masculinization of the discipline. We suggest that parents and influential adults, the primary audience of these shows, should be included in any future discussions to break down IT media stereotypes